Sobre a delimitação de Macau e Cantão. Questao de Hainan (1907)
This 1894 official correspondence, originating from the Portuguese Ministry of Foreign Affairs (General Directorate of Political and Diplomatic Affairs, 1st Division, Lisbon), concerns ecclesiastical jurisdictional disputes in southern China during the late nineteenth and early twentieth centuries. The document comprises copies of communications between the Bishop of Macau, the Secretary of State for Overseas Affairs, and the Portuguese Minister in Paris, relating to the implementation of a territorial exchange agreement between the Diocese of Macau and the Apostolic Prefecture of Canton. Central to the matter is the reciprocal transfer of jurisdictions over Hainan Island and the Shao-king (Shap Kung/Sheung-king) district, initially agreed upon following negotiations culminating in a papal decree of 16 March 1864 and reaffirmed by the Congregation for the Propagation of the Faith on 3 February 1903. The Bishop of Macau reports persistent obstruction by the Apostolic Prefect of Canton in executing the transfer, despite prior agreements and Vatican approval. Key issues include resistance from French missionaries under the Paris Foreign Missions Society, delays in handing over mission properties, and alleged diplomatic interference. The text reveals tensions between Portuguese Padroado claims and French ecclesiastical influence in China, as well as Portugal’s efforts to assert its ecclesiastical authority through diplomatic channels with both the Holy See and the French government. This document provides critical insight into colonial religious politics, Sino-European ecclesiastical diplomacy, and the decline of Portuguese ecclesiastical privileges in Asia.
Macao 2, Doc. 22
Keywords: Bishop of Macau; Canton Apostolic Prefecture; Catholic Church authority; Chao-King district; Colonial Religious Politics; Congregation for the Propagation of the Faith; Ecclesiastical Jurisdiction Dispute; French missionaries; Hainan Island jurisdiction; Jurisdictional Resistance; Macau Diocese; Mission Implementation Delays; Official Communications Copies; Papal Decree 1840; Paris Foreign Missions Society; Portuguese Colonial Administration; Portuguese Minister in Paris; Reciprocal Jurisdiction Transfer; Religious Diplomacy; Secretary of State for Overseas Affairs; Sino-Portuguese Relations; Territorial Exchange Agreement; Transcription; Vatican approval; diplomatic correspondence Lisbon; southern China missions